2021
DOI: 10.1038/s41467-020-20037-y
|View full text |Cite
|
Sign up to set email alerts
|

Experimental evidence for scale-induced category convergence across populations

Abstract: Individuals vary widely in how they categorize novel and ambiguous phenomena. This individual variation has led influential theories in cognitive and social science to suggest that communication in large social groups introduces path dependence in category formation, which is expected to lead separate populations toward divergent cultural trajectories. Yet, anthropological data indicates that large, independent societies consistently arrive at highly similar category systems across a range of topics. How is it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 42 publications
(30 reference statements)
1
23
0
Order By: Relevance
“…Together, these results suggest that fact-checkers and social media organizations can better mitigate polarization and the spread of misinformation by using more probabilistic representations of news veracity. More broadly, these results contribute to a growing body of work on networked crowdsourcing, which identifies the conditions under which communication networks can enhance the consistency and accuracy of classification systems for a range of applications [20][21][22][23]37].…”
Section: Plos Onementioning
confidence: 77%
See 1 more Smart Citation
“…Together, these results suggest that fact-checkers and social media organizations can better mitigate polarization and the spread of misinformation by using more probabilistic representations of news veracity. More broadly, these results contribute to a growing body of work on networked crowdsourcing, which identifies the conditions under which communication networks can enhance the consistency and accuracy of classification systems for a range of applications [20][21][22][23]37].…”
Section: Plos Onementioning
confidence: 77%
“…For example, it may be that individuals' mental representations of news veracity are probabilistic in nature, such that binary signaling prevents them from expressing improvements in their internal beliefs during communication [34][35][36]. Future work may also find that, since individual cognition combines both categorical and probabilistic judgments, the optimal communication modality for social learning involves a combination of categorical and binary signaling [34][35][36][37]. We anticipate that future research will benefit from exploring these questions.…”
Section: Plos Onementioning
confidence: 99%
“…This study also adds to a growing literature that has identified distinct facets of cognitive diversity in groups and new ways of measuring it-ranging from mental models (Carley and Palmquist 1992) to cognitive styles (Aggarwal and Woolley 2019) to schemas of poverty (Hunzaker and Valentino 2019) to linguistic categories (Guilbeault, Baronchelli, and Centola 2021) to discursive diversity (Lix, Goldberg, Srivastava, and Valentine 2021). Although our approach in this study focused on cognitive heterogeneity at the dyadic level, it can be readily extended to measure cognitive diversity in larger social groups.…”
Section: Cognitive Diversity In Groupsmentioning
confidence: 99%
“…Shepherd (2010), for example, has shown how the internalization of classification systems at the level of personal culture is shaped by, but also partially decoupled from, external classification systems. Guilbeault, et al (2021) explore how people converge on shared ways of classifying ambiguous tokens (cf Hebart et al 2020), specifically how groups of people come to share the same types over multiple iterations of coordination, in line with research on the development and maintenance of "arbitrary traditions" (e.g., Jacobs and Campbell 1961;Zucker 1977). In this paper, by extension, we consider how established types may change.…”
Section: Classifying and Cultural Changementioning
confidence: 99%